Synergistic anti-inflammatory and osteogenic n-HA/resveratrol/chitosan composite microspheres for osteoporotic bone regeneration - Li, Limei (Bioact Mater, 2020)
The development of functional materials for osteoporosis is ultimately required for bone remodeling. However, grafts were accompanied by increasing pro-inflammatory cytokines that impaired bone formation. In this work, nano-hydroxyapatite (n-HA)/resveratrol (Res)/chitosan (CS) composite microspheres were designed to create a beneficial microenvironment and help improve the osteogenesis by local sustained release of Res. Study of in vitro release confirmed the feasibility of n-HA/Res/CS microspheres for controlled Res release. Notably, microspheres had anti-inflammatory activity evidenced by the decreased expression of pro-inflammatory cytokines TNF-α, IL-1β and iNOS in RAW264.7 cells in a dose dependent manner. Further, enhanced adhesion and proliferation of BMSCs seeded onto microspheres demonstrated that composite microspheres were conducive to cell growth. The ability to enhance osteo-differentiation was supported by up-regulation of Runx2, ALP, Col-1 and OCN, and substantial mineralization in osteogenic medium. When implanted into bone defects in the osteoporotic rat femoral condyles, enhanced entochondrostosis and bone regeneration suggested that the n-HA/Res/CS composite microspheres were more favorable for impaired fracture healing. The results indicated that optimized n-HA/Res/CS composite microspheres could serve as promising multifunctional fillers for osteoporotic bone defect/fracture treatment.